2007
DOI: 10.1016/j.bmcl.2007.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship study of [1,2,3]thiadiazole necroptosis inhibitors

Abstract: Necroptosis is a regulated caspase-independent cell death mechanism that results in morphological features resembling non-regulated necrosis. This form of cell death can be induced in an array of cell types in apoptotic deficient conditions with death receptor family ligands. A series of [1,2,3]thiadiazole benzylamides was found to be potent necroptosis inhibitors (called necrostatins). A structure-activity relationship study revealed that small cyclic alkyl groups (i.e. cyclopropyl) and 2,6-dihalobenzylamides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…On the other hand, extensive structure-activity relationship (SAR) analysis of Nec-1 and other necrostatins revealed that even small changes to these molecules led to the robust loss of activity and failed to identify clear directions to significantly increase affinity of these moderately potent (e.g. cellular IC 50 of 7Cl-O-Nec-1=210 nM) molecules (Choi et al, 2012; Jagtap et al, 2007; Teng et al, 2005; Teng et al, 2007; Teng et al, 2008). Furthermore, necrostatins could have physical limitations on maximal robustness due to the small size of the molecules and an energy penalty due to the loss of a strong Glu/Lys interaction in αC-Glu-out conformation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, extensive structure-activity relationship (SAR) analysis of Nec-1 and other necrostatins revealed that even small changes to these molecules led to the robust loss of activity and failed to identify clear directions to significantly increase affinity of these moderately potent (e.g. cellular IC 50 of 7Cl-O-Nec-1=210 nM) molecules (Choi et al, 2012; Jagtap et al, 2007; Teng et al, 2005; Teng et al, 2007; Teng et al, 2008). Furthermore, necrostatins could have physical limitations on maximal robustness due to the small size of the molecules and an energy penalty due to the loss of a strong Glu/Lys interaction in αC-Glu-out conformation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a systematic transplantation study demonstrated that the teratoma-forming propensity of various mouse iPSC-derived neurospheres correlated with the persistence of residual undifferentiated cells (9). Because hESCs and hiPSCs also exhibit marked variations in differentiation efficiencies (and remaining undifferentiated cells) (10)(11)(12)(13), it is critical to remove all residual hiPSCs with teratoma potential before their clinical application. Despite numerous attempts at blocking teratoma formation, including introduction of suicide genes (14) or selecting the desired cell type (15), immunodepletion (16), or introducing cytotoxic antibody (17), a clinically viable strategy to eliminate teratoma formation remains to be developed (8,18).…”
mentioning
confidence: 99%
“…Recently, a series of (1,2,3)thiadiazole benzylamides were shown to be potent necroptosis inhibitors (called necrostatins) [131]. Previous reports indicated that necrostatins function as necroptosis inhibitors in FADDdeficient human Jurkat T cells following treatment with TNF- [132].…”
Section: Necroptosismentioning
confidence: 98%